APLIKASI PEMBELAJARAN AKSARA SUNDA - Anton Suhbana; Amir Murtoko (LPPM STMIK Pringsewu, 2016)
The Sundanese Script Learning application is built to facilitate the learning of Sundanese, the Sundanese script and provide knowledge to the Sundanese characters ranging from the historical to the introduction of the forms and exercises. This application made in PHP programming language. The method are used by the researchers in this study is a literature study and interview. In the design phase the authors make a structured design by using data flow diagram and dan entity relationship diagram. The results achieved for making of this application is to facilitate the users to learn Sundanese script, for get information and knowledge about the history of the Sundanese script and how about the shapes of letters of the Sundanese script and to practice the users to compose letters Sundanese script.